2017
DOI: 10.3390/nu9020180
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Iodine Fortified Milk on the Iodine Status of Lactating Mothers and Infants in an Area with a Successful Salt Iodization Program: A Randomized Controlled Trial

Abstract: Iodine deficiency during the first two years of life may cause irreversible brain damage and mental retardation. The aim of the present study was to investigate, for the first time, the effect of iodine fortified milk on the iodine status of lactating mothers and their infants. In this multicenter randomized controlled trial, 84 lactating mother-infant pairs from health care centers were randomly selected. After meeting the inclusion criteria, lactating mothers were randomly assigned to two groups: the iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Iodine supplementation (75–400 mg iodine/day) increased HM iodine concentrations ( 30 32 ), although a lower dose (75 or 150 μg/d) through either supplementation ( 31 ) or fortification ( 33 ) may be insufficient to ensure adequate iodine status in women or their infants. Equally, administering a single dose of 400 mg iodine as oral iodized oil to mothers may be an effective strategy to provide adequate iodine to their infants through HM for at least 6 months compared with direct supplementation to infants ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Iodine supplementation (75–400 mg iodine/day) increased HM iodine concentrations ( 30 32 ), although a lower dose (75 or 150 μg/d) through either supplementation ( 31 ) or fortification ( 33 ) may be insufficient to ensure adequate iodine status in women or their infants. Equally, administering a single dose of 400 mg iodine as oral iodized oil to mothers may be an effective strategy to provide adequate iodine to their infants through HM for at least 6 months compared with direct supplementation to infants ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yodkazeine has proved to be an effective means in preventing iodine deficiency in adolescents and adults. Within 6 weeks after starting consuming the iodized milk, the bodies of the examined pupils showed the normalization of iodine level, while the adults improved their sleep and increased their performance [16,17].…”
Section: Discussion Of Results Of Studying the Effect Of Using Yodkazmentioning
confidence: 99%
“…At the same time, the use of the iodized salt almost did not change the level of secretion of natural iodine. Thus, consumption of Yodkazeine can be considered as an alternative and effective method of mass prophylaxis of iodine deficiency in the country's population [16,17].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Though women had non-optimal iodine status, iodine status of their toddlers was within or near optimal levels. A possible biological explanation for this observation could be due to compensatory mechanism in the mammary glands to provide iodine enriched milk for children [35]. Though toddlers had higher iodine status, it appears the compensatory mechanism in the mammary glands strives to keep milk iodine status within or near optimal levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in consonance with other clinical trial studies [36] that show a positive improvement of median UIC by iodized salt use in toddlers. A recent study published by Nazeri and colleagues [35] reported beneficial effect of iodine fortified foods in improving the median UIC of lactating women. Another study in northern Ghana [34] reports the beneficial effect of iodine fortified bouillon cubes.…”
Section: Discussionmentioning
confidence: 99%